IMPROVING THE STUDENT'S VOCABULARY MASTERY BY USING PUZZLES AT THE FIFTH YEAR OF SDN 04 KARTASURA - HIDAYAH, NUR (2010)
The general objective of this research is to improve the students' vocabulary mastery. While, the specific objectives of this research are describing three things : the process of improving the students' mastery on vocabulary by using puzzles, the result of improving vocabulary using puzzles, and the advantages and disadvantages of learning vocabulary using puzzles. In achieving the objectives of the research, the writer uses Classroom Action Research. There are two cycles in this action research in which each cycle is conducted in three meetings: two meetings of teaching-learning process and ended by giving post test. Each cycle of this action research consist of six step: identifying the problem, planning the action, implementing the action, observing and monitoring the action, evaluating and reflecting the result of the Observation, revising the plan for the next cycle. The research held in SDN Kartasura 04. The subject of this study is (Class 5) the students of SDN Kartasura 04 that consists 15 students. In analyzing the data, the writer uses both qualitative and quantitative analysis taken from observation, test and interview. After analyzing the data, the writer described the result of research in which the mean score of pre-test is 58,5, in post test I is 83,4, and in post-test II is 95,8. It indicates that the students have an improvement in vocabulary mastery. Through puzzles, the students became more active and creative in vocabulary class. They could memorize the English word. Thus, it can be said that teaching vocabulary through puzzles is successful to improve the students' vocabulary mastery in SDN Kartasura 04.